Breaking the entangling gate speed limit for trapped-ion qubits using a phase-stable standing wave - Saner, S; Băzăvan, O; Minder, M; Drmota, P; Webb, DJ; Araneda, G; Srinivas, R; Lucas, DM; Ballance, CJ (American Physical Society, 2023)
All laser-driven entangling operations for trapped-ion qubits have hitherto been performed without control of the optical phase of the light field, which precludes independent tuning of the carrier and motional coupling. By placing 88Sr+ ions in a λ=674  nm standing wave, whose relative position is controlled to ≈λ/100, we suppress the carrier coupling by a factor of 18, while coherently enhancing the spin-motion coupling. We experimentally demonstrate that the off-resonant carrier coupling imposes a speed limit for conventional traveling-wave Mølmer-Sørensen gates; we use the standing wave to surpass this limit and achieve a gate duration of 15  μs, restricted by the available laser power.